2019
DOI: 10.5688/ajpe6782
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning a Pharmacology Course to Promote Active Learning

Abstract: Objective. To redesign a Pharmacology course to incorporate active learning sessions and explore commonly perceived barriers to implementing active learning.Methods. Upon redesign, the course met for 50 minutes 2X/week with all students in lecture and then students were divided into 1 of 3 50 minute recitations/week where they applied course concepts to cases, problems and situations. Previous iterations met 2X/week for 75 minute sessions. Data is presented from the 2 years before the redesign and 2 years afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…It is a challenge to maintain the attention of students and change the passive role of students to be active. Many research in the field of medical education also showed the same concerns [7][8][9][10][11]. Some examples of active learning in the medical context are making presentations in the form of poems, songs, and stories [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a challenge to maintain the attention of students and change the passive role of students to be active. Many research in the field of medical education also showed the same concerns [7][8][9][10][11]. Some examples of active learning in the medical context are making presentations in the form of poems, songs, and stories [8].…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of active learning in the medical context are making presentations in the form of poems, songs, and stories [8]. Lecturers can also have discussions outside the classroom [11] or create small group discussions [12] or provide Problem-Based Learning to students [13].…”
Section: Discussionmentioning
confidence: 99%
“…11 While pharmacy education has made great progress and uses many innovative teaching methods and experiential learning, [13][14][15] traditional lecture is still the primary method of content delivery, especially in pharmaceutical sciences courses such as pathophysiology. 16,17 It is difficult to ignore the potential for distraction that electronic devices may cause in these lecturebased courses, and this may be yet another reason for instructors to consider transitioning their content delivery away from lecture-based methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is likely advantages to using computers in courses that are not lecture based. For example, in the author's other courses, 16,18 students often require computers to access information to help them complete the case or problem they are exploring, and that teaching method leads to increased student performance. 16 There are limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Active learning has become a trend in higher education, especially to increase the knowledge and skills needed by scientists, including pharmacists. [1][2][3] Active learning is very appropriate to be used to build critical thinking skills and has also been proven successful in creating a more interesting learning atmosphere because it gives freedom to students to choose ways of learning that suit their needs. 4,5 Active learning has succeeded in shifting traditional teachercentered learning to student-centered learning for the achievement of competencies.…”
Section: Introductionmentioning
confidence: 99%